Sotos syndrome presenting with epilepsy - Büyükgebiz, Atilla; Kınık, Erol (The Turkish Journal of Pediatrics, 1990)
A fourteen and a half year-old boy of tall stature presenting with epilepsy was diagnosed as having Sotos syndrome (cerebral gigantism) at the Hacettepe University Children’s Hospital. Since EEG abnormalities are known manifestations in this syndrome, a case presenting with epilepsy is very rare. We believe that a presumed cerebral defect could create convulsions and would thus be the cause of cerebral gigantism whose etiology is still unclear. Thus patients with this syndrome should be followed up for the risk of epilepsy.
Keywords: Sotos syndrome; epilepsy